Beyond words How humans communicate through sound. [article]. - Kraus, Nina
Every day we communicate using complex linguistic and musical systems, yet these modern systems are the product of a much more ancient relationship with sound. When we speak, we communicate not only with the words we choose, but also with the patterns of sound we create and the movements that create them. From the natural rhythms of speech, to the precise timing characteristics of a consonant, these patterns guide our daily communication. Be examining the principles of information processing that are common to speech and music, we peel back the layers to reveal the biological foundations of human communication through sound. Further, we consider how the brain's response to sound it shaped by experience, such as musical expertise, and implications for the treatment communication disorders. -- (from the authors)